PHYSICAL PERSONS AS TOURIST SERVICE PROVIDERS IN AGRITOURISM - Veselinović, Janko (Economics of Agriculture, 2013)
The goal of the paper is to analyse the normative regulation which creates the conditions under which physical persons offer tourist services in agritourism. The results of this work identify the Law on Tourism as a good legal framework for the inclusion of physical persons who are not registered as entrepreneurs in the performance of tourism activities in rural areas. The results also confirm that agritourism is one of the forms of economic activity which does not yield significant economic results in Serbia. The paper can lead to a conclusion that the creation of a normative framework for the inclusion of a widest range of service providers in agritourism opens a host of possibilities for the development of this kind of tourism, but also the parallel development of agriculture, cattle breeding and the overall development of rural areas. New legal frameworks create possibilities for physical persons to engage in providing services of accommodation and lodging, as well as catering homemade food and drink. Lawmakers offer this possibility to the unemployed and employed alike, but also to the retired persons and even older minors – persons over 16 years of age. These legal possibilities should also be followed by certain measures of national, provincial and local institutions. The methods used are those of analysis and comparison.